Perakitan Sistem WECG IoT dan Diseminasi Unjuk Kinerja untuk Memperkuat Sistem Layanan Kesehatan Puskesmas - Kitta, Ikhlas; Palantei, Elyas; Suyuti, Ansar; Manjang, Salama; Samman, Faizal Arya; Nappu, Muhammad Bahtiar; Arief, Ardiaty; Said, Sri Mawar; ., Gassing; Gunadin, Indar Chaerah; ., Hasniaty; Adil, Andi Eri Andika; Palantei, Idris (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2025)
This community service program is focused on a number of issues such as the implementation of the wireless ECG device design and the dissemination and demonstration of its technical operations in a such manner to all participants, e.g. the activists and supporters of the sub-village community healthcare center (PUSTU) located in Malimongeng Village, Salomekko District, Bone Regency. Several models of the latest WECG devices and the latest innovations have been developed and produced independently on the UNHAS campus, both hardware and software components. This Electrocardiogram (ECG) functions to monitor the condition of heart health and blood pressure in each patient who has been fitted with an ECG device. Each wireless ECG device is connected by an internet network and integrated at once in 1 Website that displays ECG signal graphics so that it can be monitored and controlled in real time from a distance. The application of ECG is very necessary for nurses or medical teams in a health institution to facilitate the control of the condition of patients in the room without having to walk back and forth to check the condition of patients being treated. The implementation of this community service is divided into 2 stages, namely the dissemination stage of basic knowledge of ECG technology and the technical training stage for operating ECG devices to support the patient condition control system at the health center. The results of recording the level of knowledge and understanding of the Malimongeng Village community who participated in community service activities carried out by a team of researchers and inventors from the Department of Electrical Engineering, Faculty of Engineering, Hasanuddin University were documented using the Googleform questionnaire application which had been designed earlier before the implementation of the activity in such a way as to measure the level of success of the implementation of the 2024 PKM program. The questionnaire survey was distributed and filled out by PKM participants online, both before and after the provision of material. After the implementation of the dissemination agenda and demonstration of the operation of the IoT WECG technology device, there was an increase in the knowledge and general understanding of the Malimongeng Village community who participated in the LBE Excellent Collaboration community service program in 2024 in both aspects of the category, namely general knowledge of health science and technical matters related to the development and production of IoT WECG devices along with their direct application in the midst of community life. The influence of participation in the series of PKM activities on both aspects of the target of counseling/socialization resulted in an increase in the capacity of knowledge in the community, namely around 30 percent and 25 percent respectively. Aspects of Technology Benefits and Activities, Based on the recommendations and input of all PKM activity participants, the following issues are highly expected by the Malimongeng Village community, including: aspects of the quality and diversity of cutting-edge science should be formulated to be more interesting and increase the insight of the village community, aspects of the availability of more sophisticated health devices should and should be equipped as soon as possible with more sophisticated and modern health infrastructure and facilities in the village and aspects of sustainability of research and development and production to overcome the problem of the availability of health facilities in the village and nationally.